ADP-ribosylation of rainbow trout (Oncorhynchus mykiss) actin by botulinum C2 toxin. - Kodama, H (1993)
Intracellular actin of rainbow trout macrophages was ADP-ribosylated by botulinum C2 toxin, which is composed of two nonlinked protein components, component I and trypsinized component II. The actin in the supernatants of various tissue homogenates of the trout was also directly ADP-ribosylated by component I of C2 toxin, indicating that fish actin other than those of land vertebrates is susceptible to enzymatic modification by component I of C2 toxin.